Characterization of a Mushroom Mycelium Composite Material as an Eco-based Packaging Solution - Rahma Yanti T; Muhammad Asfar (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Lignocellulose is a natural material that is abundant and usually ends up getting discarded. Utilization of lignocellulose in mushroom growing media can also produce composites in addition to the production of mushroom fruit. In contrast to mushroom cultivation in general, the mycelial composite is an innovation that uses the mushroom roots (mycelia) as an adhesive glue to bind lignocellulosic materials into composites that are designed as packaging. This study investigates the characterization of packaging made from different types of lignocellulose (sawdust, straw, kapok) and types of oyster mushroom growing media (corn, sorghum, grain). The results obtained show that the type of lignocellulose has an effect on the character of the composite, which is due to the lignin content that it contains. Lignocellulosic sawdust (P1) has the best properties because it has tighter porosity (0.75µm), giving a strong composite. On the other hand, as shown by the percentage of moisture content and high water absorption, sawdust is also very sensitive to changes due to humidity and temperature changes. P1 has a moisture content of 10.84% and a water absorption of 265.39%. Mushroom mycelium composites from all treatments have a high water content compared to conventional packaging and also indicate that this packaging has the ability to decompose naturally.